Molecular transmission network of pretreatment drug resistance among human immunodeficiency virus-positive individuals and the impact of virological failure on those who received antiretroviral therapy in China - Chen, Hongli; Hu, Jing; Song, Chang; Li, Miaomiao; Zhou, Yesheng; Dong, Aobo; Kang, Ruihua; Hao, Jingjing; Zhang, Jiaxin; Liu, Xiu; Li, Dan; Feng, Yi; et al. (Frontiers in Medicine, 2022)
Objectives: We investigated the prevalence of pretreatment drug resistance (PDR), the molecular transmission network among HIV-positive individuals, and the impact of virological failure on those who received antiretroviral therapy (ART) in China Methods: Based on the World Health Organization (WHO) surveillance guidelines for PDR, a baseline survey and follow-up were conducted in 2018 and 2021, respectively. Demographic information and plasma samples were obtained from all participants. HIV pol gene region sequences were used to analyze the PDR and molecular transmission networks using the Stanford HIV database algorithm and HIV-TRACE, respectively. This study assessed the odds ratios (OR) of PDR to virological failure (viral load ≥50 copies/mL) after three years of ART using multivariable logistic regression. Results: Of the 4084 individuals, 370 (9.1%) had PDR. The prevalence of non-nucleoside reverse transcriptase inhibitors (5.2%) was notably higher than that of nucleoside reverse transcriptase inhibitors (0.7%, p <0.001), protease reverse transcriptase inhibitors (3.0%, p<0.001), and multidrug resistance (0.3%, p <0.001). A total of 1339 (32.8%) individuals from 361 clusters were enrolled in the molecular transmission network. Of the 361 clusters, 22 clusters included two or more individuals with PDR. The prevalence of virological failure among HIV-positive individuals after three years of ART without PDR, those with PDR to Chinese listed drugs, and those with PDR to other drugs was 7.9%, 14.3%, and 12.6%, respectively. Compared with HIV-positive individuals without PDR, virological failure after three years of ART was significantly higher (OR: 2.02, 95% confidence interval (CI): 1.25–3.27) and not significantly different (OR: 1.72, 95% CI: 0.87–3.43) in individuals with PDR to Chinese listed drugs and those with PDR to other drugs, respectively. Missed doses in the past month were significantly associated with virological failure (OR, 2.82; 95% CI: 4.08–5.89). Conclusions: The overall prevalence of PDR was close to a high level and had an impact on virological failure after three years of ART. Moreover, HIV drug-resistant strains were transmitted in the molecular transmission network. These results illustrate the importance of monitoring PDR and ensuring virological suppression through drug adherence.